2007 Global Hunger Index: The challenge of hunger: Global Hunger Index: Facts, determinants, and trends - Wiesmann, Doris; Sost, Ann Kathrin; Schöninger, Iris; Dalzell, Howard; Kiess, Lynnda; Arnold, Tom; Collins, Steve (Welthungerhilfe, 2007)
Because hunger has many faces, it makes sense to choose a multidimensional approach for calculating the Global Hunger Index (GHI). Such an approach has the following advantages: 1. It simultaneously captures various aspects of hunger and undernutrition. 2. The combination of indicators measured independently of each other reduces the impact of random measurement errors. 3. The condensing of information facilitates a quicker overview for decision makers in the public and political arenas.